Paediatric fever management practices and antipyretic use among doctors and nurses in New Zealand emergency departments. (29th May 2022) - Tan, Eunicia; Beck, Sierra; Haskell, Libby; MacLean, Alastair; Rogan, Alice; Than, Martin; Venning, Bridget; White, Christopher; Yates, Kim; McKinlay, Christopher JD; Dalziel, Stuart R
Abstract: Objectives: To assess (i) paediatric fever management practices among New Zealand ED doctors and nurses, including adherence to best practice guidelines; and (ii) the acceptability of a randomised controlled trial (RCT) of antipyretics for relief of discomfort in young children. Methods: A cross‐sectional survey of doctors and nurses across 11 New Zealand EDs. The primary outcome of adherence to paediatric fever management best practice guidelines was assessed with clinical vignettes and defined as single antipyretic use for the relief of fever‐related discomfort. Results: Out of 602 participants (243 doctors, 353 nurses and six unknown; response rate 47.5%), only 64 (10.6%, 95% confidence interval [CI] 8.3–13.4%) demonstrated adherence to best practice guidelines. In a febrile settled child with normal fluid intake, the percentage of participants that would use antipyretics doubled with abnormal vital signs (33.7% vs 72.9%, difference −39.2%, 95% CI –44.4% to −34.0%). Most participants would use antipyretics for reduced fluid intake ( n = 494, 82.1%, 95% CI 78.8–85.0%) in a febrile settled child. Over half ( n = 339, 57.1%, 95% CI 53.0–61.1%) would advise giving antipyretics to prevent febrile convulsions. Most ( n = 467, 80.0%, 95% CI 76.5–83.1%) participants agreed that a RCT of antipyretics in febrile children <2 years of age with relief of discomfort as a primary outcome is needed. Conclusions: Just over 10% of New Zealand ED doctors and nurses demonstrated adherence to paediatric fever management best practice guidelines. A RCT of antipyretics in febrile children <2 years of age specifically addressing relief of discomfort as a primary outcome is strongly supported.